ENHANCING FINANCIAL RESOURCE FORMATION IN BUSINESSES - Tadjibekova, Dilnoza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This paper delves into the methods of developing financial resources within businesses, particularly in the context of Uzbekistan. It highlights major challenges including restricted access to funds, regulatory barriers, and delays in technology adoption. The article suggests various strategies such as advancing the financial markets, revising regulations, diversifying sources of finance, educational and training programs, and embracing financial technologies. These strategies are designed to improve the financial robustness and market competitiveness of Uzbek businesses, thereby aiding in the country's overall economic growth.